القيافة والفراسة كوسائل إثبات - الشريف، عثمان حيدر أبو زيد (جامعة أم درمان الإسلامية - معهد البحوث والدراسات الإستراتيجية, 2006)
كان للعرب في الجاهلية بعض الأعراف التي تعد من قبيل القرائن مثل القيافة والفراسة، فالقيافة وسيلة لإلحاق الولد بأبيه عند وجود شبه بينهما وقد كانت لها مكانتها عند العرب قبل الإسلام فكانوا يعتمدون عليها في إثبات النسب، إذ وقع نزاع أو اشتباه في نسب طفل ما وأرادوا إلحاقه بمن يفترض أن ينتسب إليه وكان لهم في ذلك نتائج عظيمة. فلما جاء الإسلام لم يعمل بهذا الطريق على إطلاقه بل اعتمده كطريق للإثبات في بعض دعوي النسب. أما الفراسة فهي من التثبت والنظر والتفرس. وتعني الاستدلال بالأمر الظاهر على الأمور الخفية فتعرف بها أخلاق الناس الباطنة من النظر في أحوالهم الظاهرة. وقد ظل القضاة على مر العصور يستخدمون الفراسة للوصول إلى الحكم الصائب. Before Islam Arabs had some traditions which were considered as clues like tracking and physiognomy. Thus tracking is a means to belong the baby to its father when they are like. It has its importance for the Arabs Islam they have been depending on it to certify the parentage , when there is a conflict or doubt of a baby and it was about to be belonged to its supposed father , they have got great results and when Islam came this method was not used but it was confirmed as a method of confirmation in some of parentage cases. Physiognomy is but verification foresight and scrutinizing and it means proving with the appearance for hidden mattes so in this way the inner morals of people are known from the mental perception of their apparent conditions. Judges have been using physiognomy era after era to achieve the sound verdict.
Keywords: القيافة -- الفراسة